Application of Roboduino ATMega 2560 in the Manufacturing of Goods Moving Beetle Robots - Saut Situmorang (PT Inovasi Pratama Internasional, 2020)
In the development of science and technology in the field of electronics today, there are many benefits that can be felt by the community, one of which is facilitating work in industry and households. Technological developments in the industrial sector such as warehousing have experienced many advances, one of which is the process of moving goods more easily without human intervention but automatically so as to make the logistics process of goods more precise and accurate. The existence of processes that can run automatically can make work processes more efficient, flexible and run continuously. And often see the work of lifting goods that are very human, then a robot function is made to help make human work lighter. Control and automation can be done easily, efficiently and quickly. The control of this item moving robot uses Arduino UNO ATMega 2560 as the robot's control center. The motion system on the robot uses a motor drive, a servo motor to raise and lower the goods hook which functions to lift and lower goods and a DC motor which aims to move the robot from one place to another. The goods moving robot will work continuously until the inventory can be moved completely.